One-step flame synthesis of SnO2 / TiO2 composite nanoparticles for photocatalytic applications - Kranthi K. Akurati; Andri Vital; Roland Hany; Bastian Bommer; Thomas Graule; Markus Winterer (International Journal of Photoenergy)
SnO2 / TiO2 composite nanoparticles have been synthesized in a single-step by feeding evaporated precursor mixtures into an atmospheric pressure diffusion flame. Particles with controlled Ti: Sn ratios were produced at various flow rates of oxygen, and the resulting powders were characterized by BET surface area analysis, XRD, TEM, EDAX and UV-Vis spectroscopy. For the lowest concentration (3.4 mol %) of SnO2 employed in this study anatase phase of TiO2 is stabilized, while segregation of SnO2 is seen at medium (6.9 to 12.4 mol %) and high concentrations (20.3 mol %). Though the equilibrium phase diagram predicts complete solubility of one oxide in another at all compositions, segregation of SnO2 phase is observed which is explained by the usage of diffusion flame in the present study. The particle formation mechanism of SnO2 / TiO2 composites is proposed basing on the single component aerosol formation. Photocatalytic activity of the composite particles is tested for the degradation of methylene blue and is compared with pure TiO2 synthesized under similar conditions. Improved photocatalytic activity of the composite particles is attributed to the stabilized anatase phase and better charge separation due to the coupling of TiO2 and SnO2 within the composite nanoparticles.